2016
DOI: 10.1177/1468087415613208
|View full text |Cite
|
Sign up to set email alerts
|

Reaction-space analysis of homogeneous charge compression ignition combustion with varying levels of fuel stratification under positive and negative valve overlap conditions

Abstract: Full-cycle computational fluid dynamics simulations with gasoline chemical kinetics were performed to determine the impact of breathing and fuel injection strategies on thermal and compositional stratification, combustion and emissions during homogeneous charge compression ignition combustion. The simulations examined positive valve overlap and negative valve overlap strategies, along with fueling by port fuel injection and direct injection. The resulting charge mass distributions were analyzed prior to igniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This analysis is similar to the reactivity stratification analysis per formed by Kodavasal et al for HCCI ([54,56,57]). We observe that just based on computing ignition delays without any consider ation of the thermodynamic-time history of the charge from SOI up to that point, the -18 deg aTDC SOI case shows a shorter minimum ignition delays within the charge compared to the -30 deg aTDC SOI case, which would lead us to believe that this case would ignite before the optimum -30 deg aTDC SOI case.…”
Section: Fig 21 Tradeoff Between Shorter Ignition Delays and Reducedmentioning
confidence: 85%
“…This analysis is similar to the reactivity stratification analysis per formed by Kodavasal et al for HCCI ([54,56,57]). We observe that just based on computing ignition delays without any consider ation of the thermodynamic-time history of the charge from SOI up to that point, the -18 deg aTDC SOI case shows a shorter minimum ignition delays within the charge compared to the -30 deg aTDC SOI case, which would lead us to believe that this case would ignite before the optimum -30 deg aTDC SOI case.…”
Section: Fig 21 Tradeoff Between Shorter Ignition Delays and Reducedmentioning
confidence: 85%
“…Using this approach, the computational expense of the chemical kinetics is reduced by an order of magnitude relative to detailed chemistry in every cell. 24 The kinetics calculations in this work use a reduced 312-species reaction mechanism based on the detailed gasoline reaction mechanism from Mehl et al 25 along with the matched four-component gasoline surrogate fuel 26 shown in Table 2. This surrogate and reduced gasoline mechanism captures gasoline fuel chemistry attributes such as the low, negative temperature coefficient (NTC) and high temperature ignition predicted by the detailed parent mechanism.…”
Section: Modeling Approachmentioning
confidence: 99%
“…Using this approach, the computational expense of the chemical kinetics is reduced by an order of magnitude relative to detailed chemistry in every cell. 25 The kinetics calculations use a reduced 312-species mechanism based on the detailed gasoline mechanism from Mehl et al 32 along with the matched fourcomponent gasoline surrogate 33 shown in Table 2. This surrogate and reduced gasoline mechanism captures gasoline fuel chemistry attributes such as the low, negative temperature coefficient (NTC) and hightemperature ignition predicted by the detailed parent mechanism.…”
Section: Cfd Modelmentioning
confidence: 99%
“…Even though the temperature of the hottest charge is correctly predicted up to the time of ignition for both cases, the use of the mean composition for HCCI ignition modelling with NVO valve events may be problematic because of stratification. To assess the validity of using the mean composition along with the adiabatic core temperature for ignition modelling, the cumulative distribution of reactivity 25 is visualized with the ignition delay calculated in every CFD cell using Goldsborough's correlation 42 at the onset of ignition (u IGN = 212.5°CA). The differences in the iso-octane and gasoline ignition delays are essentially negligible for temperatures greater than 1000K [43,26].…”
Section: Adiabatic Core Ignition Modelmentioning
confidence: 99%